Pengaruh Kepemilikan Institusional, Leverage, Dan Ukuran Perusahaan Terhadap Tax Avoidance - Alya, Yuniarwati (Jurnal Paradigma Akuntansi, 2021)
The purpose of this study is to examine the analysis of the effect of institusional ownership, leverage, and firm size on tax avoidance of manufacturing companies listed on the Indonesia Stock Exchange in 2016-2018. The samples used 83 companies were selected using the purposive sampling method. Data were processed and tested using E-views version 10 dan Microsoft excel 2013. The result of this research shows that institutional ownership (INST), leverage (DAR), and firm size (SIZE) simultaneously (F test) effects on tax avoidance (ETR). The T test result shows that institutional ownership (INST) and firm size (SIZE) has no significant effect on tax avoidance. On the other hand leverage (DAR) has a negative effect and significantly on tax avoidance.